2016
DOI: 10.17744/mehc.38.4.04
|View full text |Cite
|
Sign up to set email alerts
|

Counselors’ Comfort with Sexuality, Attitudes towards Pornography, and Propensity to Assess and Treat Client Issues Related to Pornography Use

Abstract: Clients present to counseling with clinical issues related to their pornography use. However, counselors report being undertrained and unprepared to work with clients regarding issues relating to pornography. Some researchers believe counselors' personal beliefs and attitudes about sex inhibit their ability to work with clients with issues related to sexuality. Therefore, we investigated counselors' comfort with discussing issues of sexuality, counselors' attitudes towards pornography, and their propensity to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 46 publications
0
16
0
Order By: Relevance
“…Further, it is necessary to note that labels of mental illness (i.e., disorders identified in the DSM) can improperly be used to reinforce negative social beliefs (Hozid, 2013), including stereotyping and microaggressions . Clients are seeking counseling services for sexual issues (Ayres & Haddock, 2009;Goldberg et al, 2008;Harris & Hays, 2008;Bloom et al, 2016), but counselors might be holding conservative and/or progressive beliefs about sexuality (Authors , 2016) that inhibit their unbiased treatment of those problems, thus impairing their ability to fulfill their role as an ethical counselor working within their boundaries of skills and competence (ACA, 2014).…”
Section: Sexuality and The Counseling Fieldmentioning
confidence: 99%
See 4 more Smart Citations
“…Further, it is necessary to note that labels of mental illness (i.e., disorders identified in the DSM) can improperly be used to reinforce negative social beliefs (Hozid, 2013), including stereotyping and microaggressions . Clients are seeking counseling services for sexual issues (Ayres & Haddock, 2009;Goldberg et al, 2008;Harris & Hays, 2008;Bloom et al, 2016), but counselors might be holding conservative and/or progressive beliefs about sexuality (Authors , 2016) that inhibit their unbiased treatment of those problems, thus impairing their ability to fulfill their role as an ethical counselor working within their boundaries of skills and competence (ACA, 2014).…”
Section: Sexuality and The Counseling Fieldmentioning
confidence: 99%
“…A review of the literature indicates that counselors' comfort with sexuality might be a mitigating factor in the treat-ment of sexual issues (Kazukauskas & Lam, 2009;Harris & Hays, 2008;Bloom et al, 2016). Goldberg and colleagues (2008) explored marriage and family therapists' (N = 134) treatment of client issues related to cybersex and identified that 20% of their sample did not feel prepared to diagnose problems related to cybersex.…”
Section: Sexuality and The Counseling Fieldmentioning
confidence: 99%
See 3 more Smart Citations